Clinico-pathological study of ovarian tumors in Goa medical college: a tertiary care centre in Goa, India - Jindal, Manjusha; Jindal, Dweep; Sahasrabhojane, Mrinalini; Naik, Viraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ovarian neoplasms are a distinct entity in women health care and are increasingly contributing to morbidity and mortality among women. The burden is not only related to the increasing incidence but also to the varied pathological features depending on the tissue of origin and pathogenesis. The study was carried out to find the prevalence and determine the clinical presentation and histo-pathological distribution of ovarian neoplasms. Management options were also noted. Methods: It is a retrospective study carried out at Goa Medical College between January 2013 to December 2015. All patients diagnosed and treated for ovarian neoplasm were included in the study. Data was tabulated using Microsoft Excel and descriptive statistical analysis was carried out using SPSS version 23. Results: A total of 3111 patients were admitted in gynecology at Goa Medical College during the specified time period. Of these 358 cases were diagnosed with ovarian neoplasm. On histopathology 196 were benign tumors and 162 were reported to be malignant. Commonest presenting symptom was abdominal distention seen in 51.1% of the patients, pain in 44.4%, followed by dyspepsia in 26.85%. Epithelial tumors were most common (Benign - 39.3%, Malignant - 41%) followed by sex cord stromal tumors and germ cell tumors in 7.26% of cases. Conclusions: Surface epithelial tumors were most common neoplasm. An alarming high no. of malignant tumors (45.25%) was found in present study. 44.4% tumors presented in 41-50 years age group. Presenting complaints were vague and nonspecific leading to delay in diagnosis. Histological type correlates with prognosis; therefore, preponderance of histological type will guide treatment options and patient education with respect to epidemiology.